If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (6x + -3)(5x + 3) = 0 Reorder the terms: (-3 + 6x)(5x + 3) = 0 Reorder the terms: (-3 + 6x)(3 + 5x) = 0 Multiply (-3 + 6x) * (3 + 5x) (-3(3 + 5x) + 6x * (3 + 5x)) = 0 ((3 * -3 + 5x * -3) + 6x * (3 + 5x)) = 0 ((-9 + -15x) + 6x * (3 + 5x)) = 0 (-9 + -15x + (3 * 6x + 5x * 6x)) = 0 (-9 + -15x + (18x + 30x2)) = 0 Combine like terms: -15x + 18x = 3x (-9 + 3x + 30x2) = 0 Solving -9 + 3x + 30x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '3'. 3(-3 + x + 10x2) = 0 Factor a trinomial. 3((-3 + -5x)(1 + -2x)) = 0 Ignore the factor 3.Subproblem 1
Set the factor '(-3 + -5x)' equal to zero and attempt to solve: Simplifying -3 + -5x = 0 Solving -3 + -5x = 0 Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + -5x = 0 + 3 Combine like terms: -3 + 3 = 0 0 + -5x = 0 + 3 -5x = 0 + 3 Combine like terms: 0 + 3 = 3 -5x = 3 Divide each side by '-5'. x = -0.6 Simplifying x = -0.6Subproblem 2
Set the factor '(1 + -2x)' equal to zero and attempt to solve: Simplifying 1 + -2x = 0 Solving 1 + -2x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -2x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -2x = 0 + -1 -2x = 0 + -1 Combine like terms: 0 + -1 = -1 -2x = -1 Divide each side by '-2'. x = 0.5 Simplifying x = 0.5Solution
x = {-0.6, 0.5}
| 9x+83=-7x+44 | | -7+2x=4 | | -16n+16=-12n-8 | | -10=4n+n | | -9x+4=4x+4 | | Y=230+130x | | -(z+7)+(6z+1)=-5(z+1) | | -109-g=11 | | 0.3(6x+30)=1.8(x+5) | | (5b-9)-3(8-2b)=b | | i=pod | | -3y-9=6y+27 | | .33(k+15)=2k+2 | | n=2py^3-5px | | 7m+21=35+24m | | 0.2x-0.6666667(x-8)=6x | | 4q+3q-1=5-q | | 7z+10=7(z+3) | | 7+21m=35+24m | | -0.2x=6 | | 8m-5m=9 | | -4(k-1)=4 | | 0.5m=m+10 | | -110+1x+7x=58 | | 2p-9=15g-9 | | 19x+51x-16=10(7x+15) | | a+4=13-2a | | 3(m+1)=-4(-2-m)+2 | | F(n)=150-20n | | 2(3-x)=10 | | xC=S-C | | x+4*2=6x |